A high-hardness environmentally friendly green oil for 5G high frequency and its preparation method
By using unsaturated polyester modified acrylic resin with a glass transition temperature of 80-100°C and a specific UV monomer and insulating powder filler, the insufficient hardness and adhesion performance of environmentally friendly green oil in 5G high-frequency environments is solved. The problem is that high hardness, excellent insulation and stability are achieved, ensuring signal transmission and environmentally friendly performance.
Patent Information
- Application Number
- CN202411412093.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-11
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of environmentally friendly green oil technology, and in particular to a high-hardness environmentally friendly green oil for 5G high frequency and a preparation method thereof. Background Art
[0002] With the rapid development of 5G technology, electronic devices have higher and higher requirements for high-frequency signal transmission, which also puts higher requirements on electronic circuit boards. Among them, in the manufacturing process of electronic circuit boards, environmentally friendly green oil is used to protect the metal lines on electronic circuit boards from interference and corrosion from the external environment, and is a key protective material. At present, in order to reduce signal interference and increase the service life of electronic equipment in the 5G high-frequency environment, environmentally friendly green oil needs to have better insulation performance, hardness performance and adhesion performance. Summary of the invention
[0003] In order to obtain an environmentally friendly green oil that can be used in a 5G high-frequency environment, the present application provides a high-hardness environmentally friendly green oil for 5G high frequency and a preparation method thereof.
[0004] In the first aspect, the present application provides a 5G high-frequency high-hardness environmentally friendly green oil adopts the following technical solution:
[0005] A high-hardness environmentally friendly green oil for 5G high frequency, comprising 55-60 parts by weight of unsaturated polyester modified acrylic resin, 4-5 parts by weight of UV monomer, 9.5-10.8 parts by weight of photoinitiator, 17.5-19.4 parts by weight of insulating powder filler, 1-2 parts by weight of color powder and 10-15 parts by weight of solvent; wherein the glass transition temperature of the unsaturated polyester modified acrylic resin is 80-100°C, and the number of double bond functional groups in the UV monomer is 3-6.
[0006] In this application, the high-hardness environmentally friendly green oil for 5G high frequency uses an unsaturated polyester modified acrylic resin with a glass transition temperature of 80-100°C as a connecting resin, and limits the number of double bond functional groups in the UV monomer to 3-6. At the same time, combined with the ratio of the raw materials of each component, it is beneficial to obtain an environmentally friendly green oil with high cross-linking degree, high hardness, and scratch resistance suitable for 5G high frequency. In addition, the environmentally friendly green oil of this application has good insulation and insulation stability, which can ensure the stable transmission of signals, and is especially suitable for 5G high frequency. At the same time, the environmentally friendly green oil of this application is also free of lead, mercury, cadmium, hexavalent chromium, polybrominated biphenyls and polybrominated diphenyl ethers, meets ROHS testing standards, and has environmentally friendly performance.
[0007] In some specific embodiments, the unsaturated polyester modified acrylic resin is a reaction product obtained by copolymerizing unsaturated polyester, alkyl methacrylate, glycidyl methacrylate, and styrene in a weight ratio of (38-44): (20-25): (14.2-16.4): (30-35).
[0008] In the present application, the unsaturated polyester modified acrylic resin is preferably an unsaturated polyester modified acrylic resin obtained by copolymerizing unsaturated polyester, alkyl methacrylate, glycidyl methacrylate and styrene within the above-mentioned weight ratio range, which can obtain an unsaturated polyester modified acrylic resin with a glass transition temperature in the range of 80-100°C, while further improving the adhesion of the environmentally friendly green oil to the electronic circuit board.
[0009] In some specific embodiments, the unsaturated polyester is a reaction product of phthalic anhydride, maleic anhydride, 1,2-propylene glycol, and neopentyl glycol in a molar ratio of (1-1.2): (0.8-1): (0.8-1): (1-1.2).
[0010] In the present application, the unsaturated polyester is preferably obtained by reacting phthalic anhydride, maleic anhydride, 1,2-propylene glycol and neopentyl glycol in a specific molar ratio, which is beneficial to further improve the adhesion between the environmentally friendly green oil and the electronic circuit board and to increase the service life of the environmentally friendly green oil.
[0011] In some specific embodiments, the alkyl methacrylate is at least one of methyl methacrylate, ethyl methacrylate, and butyl methacrylate.
[0012] In some specific embodiments, the UV monomer is at least one of trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxy trimethylolpropane triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, and dipentaerythritol hexaacrylate.
[0013] In some specific embodiments, the UV monomer is a composition of tris(2-hydroxyethyl)isocyanurate triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate, and dipentaerythritol hexaacrylate in a weight ratio of (2-3): (1-2): (2-3): (3-4);
[0014] Alternatively, the UV monomer is a composition of tris(2-hydroxyethyl)isocyanurate triacrylate, pentaerythritol triacrylate, propoxylated pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate in a weight ratio of 2-3):(1-2):(2-3):(3-4).
[0015] In the present application, the UV monomer adopts tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate or a composition of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, propoxylated pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate in a weight ratio of 2-3):(1-2):(2-3):(3-4), which is conducive to obtaining an environmentally friendly green oil with high crosslinking degree, high hardness and scratch resistance, and at the same time improves the adhesion of the environmentally friendly green oil to the electronic circuit board.
[0016] In some specific embodiments, the photoinitiator is at least one of photoinitiator 819, photoinitiator 907 and photoinitiator TPO.
[0017] In some specific embodiments, the insulating powder filler is silicon dioxide with a particle size ranging from 4 to 8 μm.
[0018] Silicon dioxide with a particle size range of 4-8 μm will not affect the insulation performance of the environmentally friendly green oil, but can increase the hardness of the environmentally friendly green oil and improve the scratch resistance of the environmentally friendly green oil.
[0019] In some specific embodiments, the color powder is at least one of phthalocyanine green, cobalt green, and cobalt titanium green.
[0020] In a second aspect, the present application provides a method for preparing an environmentally friendly green oil, which is obtained by uniformly dispersing an unsaturated polyester modified acrylic resin, a UV monomer, a photoinitiator, an insulating powder filler, and a color powder in a solvent.
[0021] In summary, this application at least includes the following beneficial technical effects:
[0022] (1) In this application, the high-hardness environmentally friendly green oil for 5G high frequency uses an unsaturated polyester modified acrylic resin with a glass transition temperature of 80-100°C as a connecting resin, and limits the number of double bond functional groups in the UV monomer to 3-6. At the same time, combined with the ratio of the raw materials of each component, it is conducive to obtaining an environmentally friendly green oil with high cross-linking degree, high hardness, and scratch resistance suitable for 5G high frequency. In addition, the environmentally friendly green oil of this application has good insulation and insulation stability, which can ensure the stable transmission of signals, and is especially suitable for 5G high frequency. At the same time, the environmentally friendly green oil of this application is also free of lead, mercury, cadmium, hexavalent chromium, polybrominated biphenyls and polybrominated diphenyl ethers, meets the ROHS testing standards, and has environmentally friendly performance.
[0023] (2) In the present application, the UV monomer is tri(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate or a composition of tri(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, propoxylated pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate in a weight ratio of 2-3):(1-2):(2-3):(3-4), which is conducive to obtaining an environmentally friendly green oil with high crosslinking degree, high hardness and scratch resistance, and at the same time improving the adhesion of the environmentally friendly green oil to the electronic circuit board. DETAILED DESCRIPTION
[0024] The present application is further described below in conjunction with specific experiments.
[0025] Preparation Example
[0026] [Preparation Example 1]
[0027] Unsaturated polyester modified acrylic resin includes 38 kg of unsaturated polyester, 25 kg of alkyl methacrylate, 14.2 kg of glycidyl methacrylate, 35 kg of styrene, 1.2 kg of initiator, 0.1 kg of chain transfer agent and 20 kg of diluent.
[0028] Among them, the unsaturated polyester is the product of esterification and polycondensation of phthalic anhydride, maleic anhydride, 1,2-propylene glycol and neopentyl glycol in a molar ratio of 1:1:0.8:1.2 under the catalysis of tetrabutyl titanate. The specific preparation method of the unsaturated polyester is as follows:
[0029] 1 kmol of phthalic anhydride, 1 kmol of maleic anhydride, 0.8 kmol of 1,2-propylene glycol, 1.2 kmol of neopentyl glycol, 1.2 kg of tetrabutyl titanate and 5 kg of xylene were put into a reactor, heated to 220°C and reacted for 4 hours, then 0.1 kmol of butanol was added to terminate the reaction, and then impurities were removed to obtain unsaturated polyester.
[0030] The alkyl methacrylate uses methyl methacrylate.
[0031] The initiator is a combination of azobisisobutyronitrile and benzoyl peroxide, and the weight ratio of azobisisobutyronitrile to benzoyl peroxide is 1:1.
[0032] The chain transfer agent used was dodecyl mercaptan.
[0033] The diluent used was 5-(dimethylamino)-2-methyl-5-oxopentanoic acid methyl ester.
[0034] In addition, the preparation method of unsaturated polyester modified acrylic resin is as follows:
[0035] The unsaturated polyester is added to the diluent, stirred and dispersed evenly, and then alkyl methacrylate, glycidyl methacrylate, chain transfer agent and initiator are added, and the temperature is raised to 78° C. to react for 4.5 hours, and the unreacted monomer is removed to obtain an unsaturated polyester modified acrylic resin.
[0036] According to the test, the glass transition temperature of the unsaturated polyester modified acrylic resin is 80-100°C.
[0037] [Preparation Example 2]
[0038] Unsaturated polyester modified acrylic resin includes 44 kg unsaturated polyester, 20 kg alkyl methacrylate, 16.4 kg glycidyl methacrylate, 30 kg styrene, 1.0 kg initiator, 0.15 kg chain transfer agent and 25 kg diluent.
[0039] Among them, the unsaturated polyester is the reaction product of esterification and polycondensation of phthalic anhydride, maleic anhydride, 1,2-propylene glycol and neopentyl glycol in a molar ratio of 1.2:0.8:1:1 under the catalysis of tetrabutyl titanate. The specific preparation method of the unsaturated polyester is as follows:
[0040] 1.2 kmol of phthalic anhydride, 0.8 kmol of maleic anhydride, 1 kmol of 1,2-propylene glycol, 1 kmol of neopentyl glycol, 1.0 kg of tetrabutyl titanate and 5 kg of xylene were put into a reactor, heated to 240°C for reaction for 3 hours, then 0.1 kmol of butanol was added to terminate the reaction, and then impurities were removed to obtain unsaturated polyester.
[0041] The alkyl methacrylate used is butyl methacrylate.
[0042] The initiator is a combination of azobisisobutyronitrile and benzoyl peroxide, and the weight ratio of azobisisobutyronitrile to benzoyl peroxide is 2:1.
[0043] The chain transfer agent used was dodecyl mercaptan.
[0044] The diluent used was 5-(dimethylamino)-2-methyl-5-oxopentanoic acid methyl ester.
[0045] In addition, the preparation method of unsaturated polyester modified acrylic resin is as follows:
[0046] The unsaturated polyester is added to the diluent, stirred and dispersed evenly, and then alkyl methacrylate, glycidyl methacrylate, chain transfer agent and initiator are added, the temperature is raised to 82° C. and reacted for 4 hours, and the unreacted monomer is removed to obtain an unsaturated polyester modified acrylic resin.
[0047] According to the test, the glass transition temperature of the unsaturated polyester modified acrylic resin is 80-100°C.
[0048] [Preparation Example 3]
[0049] The unsaturated polyester modified acrylic resin is different from [Preparation Example 1] in that the unsaturated polyester is different. In this preparation example, the preparation method of the unsaturated polyester is as follows:
[0050] 2 kmol of phthalic anhydride, 0.8 kmol of 1,2-propylene glycol, 1.2 kmol of neopentyl glycol, 1.2 kg of tetrabutyl titanate and 5 kg of xylene were put into a reactor, heated to 220°C for 4 hours, then 0.1 kmol of butanol was added to terminate the reaction, and then impurities were removed to obtain unsaturated polyester.
[0051] According to the test, the glass transition temperature of the unsaturated polyester modified acrylic resin is 80-100°C.
[0052] [Preparation Example 4]
[0053] The unsaturated polyester modified acrylic resin is different from [Preparation Example 1] in that the unsaturated polyester is different. In this preparation example, the preparation method of the unsaturated polyester is as follows:
[0054] 1 kmol of phthalic anhydride, 1 kmol of maleic anhydride, 2 kmol of 1,2-propylene glycol, 1.2 kg of tetrabutyl titanate and 5 kg of xylene were put into a reactor, heated to 220°C for 4 hours, then 0.1 kmol of butanol was added to terminate the reaction, and then impurities were removed to obtain unsaturated polyester.
[0055] According to the test, the glass transition temperature of the unsaturated polyester modified acrylic resin is 80-100°C. Example
[0056] [Example 1]
[0057] A high-hardness environmentally friendly green oil for 5G high frequency, including 55kg of unsaturated polyester modified acrylic resin, 5kg of UV monomer, 10.8kg of photoinitiator, 17.5kg of insulating powder filler, 1kg of color powder and 15kg of solvent.
[0058] The unsaturated polyester modified acrylic resin is the unsaturated polyester modified acrylic resin prepared in [Preparation Example 1].
[0059] The UV monomer is specifically a composition of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate, wherein the weight ratio of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate is 2:2:3:3.
[0060] The photoinitiator specifically uses photoinitiator TPO.
[0061] The insulating powder filler specifically uses silicon dioxide with a particle size range of 4-8 μm.
[0062] Specifically, phthalocyanine green is used as the toner.
[0063] The solvent used was specifically 5-(dimethylamino)-2-methyl-5-oxopentanoic acid methyl ester.
[0064] [Example 2]
[0065] A high-hardness environmentally friendly green oil for 5G high frequency, including 60kg of unsaturated polyester modified acrylic resin, 4kg of UV monomer, 9.5kg of photoinitiator, 19.4kg of insulating powder filler, 2kg of color powder and 10kg of solvent.
[0066] The unsaturated polyester modified acrylic resin is the unsaturated polyester modified acrylic resin prepared in [Preparation Example 2].
[0067] The UV monomer is specifically a composition of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate, and dipentaerythritol hexaacrylate, wherein the weight ratio of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, propoxylated pentaerythritol tetraacrylate, and dipentaerythritol hexaacrylate is 3:1:2:4.
[0068] The photoinitiator specifically used is photoinitiator 907.
[0069] The insulating powder filler specifically uses silicon dioxide with a particle size range of 4-8 μm.
[0070] Specifically, phthalocyanine green is used as the toner.
[0071] The solvent used was specifically 5-(dimethylamino)-2-methyl-5-oxopentanoic acid methyl ester.
[0072] [Example 3]
[0073] A high-hardness environmentally friendly green oil for 5G high frequency, which differs from [Example 1] in that the unsaturated polyester modified acrylic resin adopts the unsaturated polyester modified acrylic ester resin prepared by [Preparation Example 3].
[0074] [Example 4]
[0075] A high-hardness environmentally friendly green oil for 5G high frequency, which differs from [Example 1] in that the unsaturated polyester modified acrylic resin adopts the unsaturated polyester modified acrylic ester resin prepared by [Preparation Example 4].
[0076] [Example 5]
[0077] A high-hardness environmentally friendly green oil for 5G high frequency, which is different from [Example 1] in that the UV monomer is different. In this embodiment, the UV monomer is dipentaerythritol hexaacrylate.
[0078] [Example 6]
[0079] A high-hardness environmentally friendly green oil for 5G high frequency, which is different from [Example 1] in that the UV monomer is different. In this embodiment, the UV monomer is a composition of ethoxylated pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate, and the weight ratio of ethoxylated pentaerythritol tetraacrylate to dipentaerythritol hexaacrylate is 1:1.
[0080] [Example 7]
[0081] A high-hardness environmentally friendly green oil for 5G high frequency, which is different from [Example 1] in that the UV monomer is different. In this embodiment, the UV monomer is a composition of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate, and dipentaerythritol hexaacrylate, and the weight ratio of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate, and dipentaerythritol hexaacrylate is 1:1:1:7.
[0082] [Example 8]
[0083] A high-hardness environmentally friendly green oil for 5G high frequency, which is different from [Example 1] in that the UV monomer is different. In this embodiment, the UV monomer is a composition of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, and ethoxylated pentaerythritol tetraacrylate, and the weight ratio of tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate, and ethoxylated pentaerythritol tetraacrylate is 1:1:8.
[0084] Comparative Example
[0085] [Comparative Example 1]
[0086] An environmentally friendly green oil, which is different from [Example 1] in that the dosage of unsaturated polyester modified acrylic resin and insulating powder filler is different. In this comparative example, the dosage of unsaturated polyester modified acrylic resin is 70kg, and the dosage of insulating powder filler is 10kg.
[0087] Performance testing
[0088] The environmentally friendly green oil prepared in each embodiment and comparative example was applied to a 5G high-frequency electronic circuit board. During the UV curing process, the curing energy selected was 800 mj / cm 2 , the curing time is 15s, and then the following performance tests are carried out:
[0089] Hardness: The hardness of the samples was tested using a QHQ pencil scratch hardness tester. The results are shown in Table 1.
[0090] Insulation resistance test: Place the sample in a normal temperature and humidity environment for 24 hours, then test the initial resistance of the sample, then place the sample in 65℃, 90%RH for 24 hours. After the sample is out of the box, observe whether there are obvious white spots, bubbles and other damages on the surface of all test samples and measure the final insulation resistance. The test voltage is DC100V, and the initial resistance and final resistance are recorded in Table 1.
[0091] Adhesion: The adhesion of the ink layer was tested using a QEZ-Ⅱ adhesion tester and calculated using the hundred-grid method. The test results are recorded in Table 1, where the test results are expressed as 100 / A. The closer the value of A is to 100, the better the adhesion.
[0092] Table 1
[0093]
[0094] Combining Example 1 with Comparative Example 1 and the test results in Table 1, it can be seen that when the amount of unsaturated polyester modified acrylic resin in the environmentally friendly green oil increases and the amount of insulating powder filler decreases, the hardness of the environmentally friendly green oil decreases, the stability of the insulation resistance decreases, and the adhesion strength between the environmentally friendly green oil and the substrate also decreases.
[0095] Combining Example 1 with Examples 3-4 and the test results in Table 1, it can be seen that the unsaturated polyester used in the unsaturated polyester-modified acrylic resin in the environmentally friendly green oil is preferably an unsaturated polyester obtained by reacting phthalic anhydride, maleic anhydride, 1,2-propylene glycol, and neopentyl glycol in a specific molar ratio. While obtaining an environmentally friendly green oil with high hardness and good insulation, it can further improve the adhesion of the environmentally friendly green oil to the electronic circuit board.
[0096] Combining Example 1 with Examples 5-8 and the test results in Table 1, it can be seen that the UV monomer uses a composition of tris(2-hydroxyethyl)isocyanurate triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate, and dipentaerythritol hexaacrylate in a weight ratio of (2-3): (1-2): (2-3): (3-4), which can obtain an environmentally friendly green oil with high hardness and good insulation while further improving the adhesion of the environmentally friendly green oil to the electronic circuit board.
[0097] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-hardness environmentally friendly green oil for 5G high frequency, characterized by: The invention comprises 55-60 parts by weight of unsaturated polyester modified acrylic resin, 4-5 parts by weight of UV monomer, 9.5-10.8 parts by weight of photoinitiator, 17.5-19.4 parts by weight of insulating powder filler, 1-2 parts by weight of color powder and 10-15 parts by weight of solvent; wherein the glass transition temperature of the unsaturated polyester modified acrylic resin is 80-100° C., and the number of double bond functional groups in the UV monomer is 3-6; The UV monomer is a composition of tris(2-hydroxyethyl)isocyanurate triacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate in a weight ratio of (2-3):(1-2):(2-3):(3-4); Alternatively, the UV monomer is a composition of tris(2-hydroxyethyl)isocyanurate triacrylate, pentaerythritol triacrylate, propoxylated pentaerythritol tetraacrylate, and dipentaerythritol hexaacrylate in a weight ratio of (2-3):(1-2):(2-3):(3-4).
2. The high-hardness environmentally friendly green oil for 5G high frequency according to claim 1, characterized in that: The unsaturated polyester modified acrylic resin is a reaction product obtained by copolymerizing unsaturated polyester, alkyl methacrylate, glycidyl methacrylate and styrene in a weight ratio of (38-44): (20-25): (14.2-16.4): (30-35).
3. The high-hardness environmentally friendly green oil for 5G high frequency according to claim 2 is characterized by: The unsaturated polyester is a reaction product obtained by reacting phthalic anhydride, maleic anhydride, 1,2-propylene glycol and neopentyl glycol in a molar ratio of (1-1.2):(0.8-1):(0.8-1):(1-1.2).
4. The high-hardness environmentally friendly green oil for 5G high frequency according to claim 2 is characterized by: The alkyl methacrylate is at least one of methyl methacrylate, ethyl methacrylate and butyl methacrylate.
5. A 5G high-frequency high-hardness environmentally friendly green oil according to any one of claims 1-4, characterized in that: The photoinitiator is at least one of photoinitiator 819, photoinitiator 907 and photoinitiator TPO.
6. A 5G high-frequency high-hardness environmentally friendly green oil according to any one of claims 1-4, characterized in that: The insulating powder filler is silicon dioxide with a particle size range of 4-8 μm.
7. A 5G high-frequency high-hardness environmentally friendly green oil according to any one of claims 1-4, characterized in that: The color powder is at least one of phthalocyanine green, cobalt green and cobalt titanium green.
8. A method for preparing high-hardness environmentally friendly green oil for 5G high frequency as claimed in any one of claims 1 to 7, characterized in that: The unsaturated polyester modified acrylic resin, UV monomer, photoinitiator, insulating powder filler and color powder are uniformly dispersed in a solvent to obtain the product.
Citation Information
Patent Citations
Preparation method of high temperature and yellowing resistant alkali-soluble epoxy acrylate UV resin
CN104086701A
Environment-friendly nano leather coating agent as well as preparation method and preparation equipment thereof
CN110616022A
Insulating ink for photovoltaic module as well as preparation method and application of insulating ink
CN118344767A
